2017
DOI: 10.1016/j.ssmph.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Education, race/ethnicity, and multimorbidity among adults aged 30–64 in the National Health Interview Survey

Abstract: BackgroundDemographic risk factors for multimorbidity have been identified in numerous population-based studies of older adults; however, there is less data on younger populations, despite the fact that approximately 24% of US adults age 18+ have multimorbidity. Understanding multimorbidity earlier in the life course is critical because of the increased likelihood of long-term disability and loss of productivity associated with chronic disease progression.ObjectiveTo examine the associations of education and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 41 publications
8
78
2
2
Order By: Relevance
“…Our results showed that 39.0% of NHW adults had multimorbidity, higher than other published studies that used the NHIS data [31,44,45,79]. The discrepancy may be caused by differences in the study period, age composition, and the selection of chronic conditions.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Our results showed that 39.0% of NHW adults had multimorbidity, higher than other published studies that used the NHIS data [31,44,45,79]. The discrepancy may be caused by differences in the study period, age composition, and the selection of chronic conditions.…”
Section: Discussioncontrasting
confidence: 76%
“…We did not include other racial/ethnic groups such as Hispanic or Latinos and African Americans because many studies have compared multimorbidity prevalence among Hispanics and NHWs and African Americans and NHWs [44][45][46][47]. These studies reported that Non-Hispanic Blacks had greater odds of multimorbidity compared to NHWs after adjusting for other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sex, several epidemiological studies have explored whether there are associations between multimorbidity and ethnicity, and examples of these studies are detailed more fully in Annex 7. 314,315,316,317,318,319,320,321 However, differences in study methodology and in the terminology used to describe ethnicity have meant that such work is difficult to synthesise and interpret. As a result, whether there are real inter-ethnic differences in the risk of developing multimorbidity -as opposed to rates of diagnosis or differential survival -remains to be determined.…”
Section: Ethnicitymentioning
confidence: 99%
“…Cross-sectional studies investigating multimorbidity prevalence in HICs have shown a negative (or inverse) relationship between multimorbidity and socioeconomic status (SES); that is, lower SES is associated with an increased prevalence of multimorbidity. 329,330,331,332,333,334,335,336,337,338 4. Determinants of multimorbidity Notably, one cross-sectional study of a primary care population in Scotland found that the onset of multimorbidity occurred 10 to 15 years earlier in those living in the most deprived areas compared with the most affluent (see Figure 4), and that the prevalence of multimorbidity including mental health conditions was almost twice as high in the most deprived areas compared with the most affluent areas.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…It has a prevalence of between 12.9% and 95.1%, depending on case definition and populations studied, and has fairly consistently been found to be associated with increasing age, lower socio-economic status and female gender in the general population (Violan et al 2014). A relationship between multimorbidity and ethnicity has also been observed in some populations, with a higher prevalence generally found among some minority ethnic populations (Mathur et al 2011;Ahmadi et al 2016;Johnson-Lawrence et al 2017).…”
Section: Introductionmentioning
confidence: 99%